Anthropometric and motor characteristics of young handball players for the purpose of early selection - Grujic, S.; Peric, D.; Ahmetovic, Z.; Okicic, T.; Isakovic, M. (Facta Universitatis: Series Physical Education and Sport, 2018)
This paper deals with recognizing the indicators significant for early selection in handball. The sample consisted of 311 selected young players (175 males and 136 females), of the ages of between 12 and 16, who had trained handball for a minimum of 3 years. They have been tested by assemblies of young representative selections of the Handball Federation of Vojvodina. Three anthropometric variables were applied (Mass, Height, BMI), 8 tests of the Eurofit battery for the evaluation of motor abilities, and 3 tests with a ball that contained basic technical elements of handball. A factorial analysis for both genders was conducted individually, in order to establish model characteristics of young handball male and female athletes. For the subsample of girls, where three qualitatively different groups existed (the national, regional and club level), a canonical analysis was also conducted. Both subsamples resulted in a bi-component structure. With boys, the first component was formed from general motor skills, and the second from physical dimensionality. With girls, both components were similarly saturated, but they had reversed hierarchy (the first factor was formed from anthropometric, and the second from motor skills variables). A boy and a girl that are distinguished from their peers by a higher physical strength and larger physical constitution were used as the typical model of beginner handball players. In the sub-sample of girls, two canonical factors were gained, but neither was significantly discriminable. The Eurofit battery of tests did not prove to be discriminatory enough in the selection of young handball players.